The Realisation of syntactic principles in non-standard Afrikaans: the correspondence of Jan Jonker Afrikaner (1820-1889) - Luijks, Catharina Adriana Dimphina Maria (Department of English Language and Literature, 2023)
This study compares the syntax of nineteenth-century Orange River Afrikaans with Dutch and synchronic Afrikaans varieties, with particular attention to Griqua Afrikaans. It provides an account of the differences that are found between the earliest attestations of an extraterritorial variety of the Dutch language on southern African soil (the so-called Cape Dutch Vernacular) with the present-day outcome. The data collected for this study originate chiefly from an hitherto undisclosed corpus of letters kept in the Namibian State Archives by the so-called Oorlam-Nama, people of mixed descent who lived on the periphery of the nineteenth- century Cape colonial society. This thesis argues that nineteenth-century Orange River Afrikaans is a representative continuation of the earliest developments in the linguistic contact situation that existed at the Cape. The thesis advances that literacy and social class are important factors in the assessment of the written record from the Dutch colony at the Cape. The thesis centers around the letters by one author, Jan Jonker Afrikaner, written over a period of nearly twenty years in the second half of the nineteenth century. This legacy is a unique contribution to the diachronic data concerning the development of Afrikaans. From the data it is shown that this author had the command over different registers, fluctuating between a near perfect metropolitan Dutch and a Hollands that is classified as basilectal Afrikaans. The comparison of the data is set in a framework inspired by the concepts put forward in Generative Grammar. This has precipitated an exciting linguistic comparison of contemporary Afrikaans grammar with the diachronic material. This dissertation challenges the idea that the Khoesan Languages were of no or little influence in the development of Afrikaans. The linguistic analysis of the nineteenth-century data reveal that the developments which took place cannot be attributed to one single origin. It is demonstrated that the innovations and change that can be identified run parallel to regular patterns that are found in other languages generally classified as creole languages. It is argued that the syntax of the Khoesan languages is a major reinforcing factor in the development of the syntactic idiosyncrasies that are identified as un-Germanic characteristics of Afrikaans. Limited to nonstandard varieties of Afrikaans, in the concluding sections the question is raised how these findings are to be addressed in the larger context of language change.